Assessing the economic impacts of climate change: An updated CGE point of view - Francesco Bosello; Fabio Eboli; Roberta Pierfederici (Fondazione Eni Enrico Mattei (FEEM), 2012)
The present research describes a climate change integrated impact assessment exercise, whose economic evaluation is based on a CGE approach and modeling effort. Input to the CGE model comes from a wide although still partial set of up-to-date bottom-up impact studies. Estimates indicate that a temperature increase of 1.92°C compared to pre-industrial levels in 2050 could lead to global GDP losses of approximately 0.5% compared to a hypothetical scenario where no climate change is assumed to occur. Northern Europe is expected to benefit from the evaluated temperature increase (+0.18%), while Southern and Eastern Europe are expected to suffer from the climate change scenario under analysis (-0.15% and -0.21% respectively). Most vulnerable countries are the less developed regions, such as South Asia, South-East Asia, North Africa and Sub-Saharan Africa. In these regions the most exposed sector is agriculture, and the impact on crop productivity is by far the most important source of damages. It is worth noting that the general equilibrium estimates tend to be lower, in absolute terms, than the bottom-up, partial equilibrium estimates. The difference is to be attributed to the effect of market-driven adaptation. This partly reduces the direct impacts of temperature increases, leading to lower damage estimates. Nonetheless these remain positive and substantive in some regions. Accordingly, market-driven adaptation cannot be the solution to the climate change problem.
Keywords: C68; Q51; Q54; 330; Computable General Equilibrium Modeling; Impact Assessment; Climate Change